2020
DOI: 10.18294/sc.2020.3100
|View full text |Cite
|
Sign up to set email alerts
|

Consumos de sustancias psicoactivas: del castigo al cuidado

Abstract: Si bien los consumos de sustancias psicoactivas son una práctica que se remonta a los albores de la humanidad, en el último siglo se han constituido en un problema que interpela a la comunidad científica, a las agencias estatales de control, a los profesionales que actúan en los más diversos ámbitos, a la comunidad toda. Siendo una cuestión compleja que se expresa en múltiples manifestaciones, se ha tendido a circunscribirla como enfermedad y/o como delito; sin embargo, no todas las formas de consumo represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, studies show that this behavior is still frequent and has significant consequences, including among professionals in Latin America (Ronzani & Touzé, 2020). In this region, although the use of alcohol and other drugs is also an important public health problem (Medina-Mora et al, 2021) and is a behavior encouraged mainly among men by sexist culture (Ronzani, 2018), this is one of the main barriers to treatment due to structural stigma, also common among Latin-American professionals (Ronzani & Touzé, 2020; Tostes et al, 2020). Some studies have been conducted on stigma toward PUDs among health professionals and have demonstrated moralization, negative behaviors, and social distancing by professionals (Gómez et al, 2021; Santos et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies show that this behavior is still frequent and has significant consequences, including among professionals in Latin America (Ronzani & Touzé, 2020). In this region, although the use of alcohol and other drugs is also an important public health problem (Medina-Mora et al, 2021) and is a behavior encouraged mainly among men by sexist culture (Ronzani, 2018), this is one of the main barriers to treatment due to structural stigma, also common among Latin-American professionals (Ronzani & Touzé, 2020; Tostes et al, 2020). Some studies have been conducted on stigma toward PUDs among health professionals and have demonstrated moralization, negative behaviors, and social distancing by professionals (Gómez et al, 2021; Santos et al, 2015).…”
mentioning
confidence: 99%
“…Among health professionals, negative attitudes about PUDs are significant barriers to treatment (Merrick et al, 2022). However, studies show that this behavior is still frequent and has significant consequences, including among professionals in Latin America (Ronzani & Touzé, 2020). In this region, although the use of alcohol and other drugs is also an important public health problem (Medina-Mora et al, 2021) and is a behavior encouraged mainly among men by sexist culture (Ronzani, 2018), this is one of the main barriers to treatment due to structural stigma, also common among Latin-American professionals (Ronzani & Touzé, 2020;Tostes et al, 2020).…”
mentioning
confidence: 99%